The effect of Vitamin-K1 and Colchicine on Vascular Calcification Activity in subjects with Diabetes Mellitus (ViKCoVaC): A double-blind 2x2 factorial randomized controlled trial - Bellinge, Jamie W.; Francis, Roslyn J; Lee, Sing Ching; Vickery, Alistair; Macdonald, William; Gan, Seng Khee; Chew, Gerard T.; Phillips, Michael; Lewis, Joshua R.; Watts, Gerald F.; Schultz, Carl J. (Journal of nuclear cardiology, 2022)
There is currently no treatment for attenuating progression of arterial calcification. 18F-sodium fluoride positron emission tomography (18F-NaF PET) locates regions of calcification activity. We tested whether vitamin-K1 or colchicine affected arterial calcification activity. 154 patients with diabetes mellitus and coronary calcification, as detected using computed tomography (CT), were randomized to one of four treatment groups (placebo/placebo, vitamin-K1 [10 mg/day]/placebo, colchicine [0.5 mg/day]/placebo, vitamin-K1 [10 mg/day]/ colchicine [0.5 mg/day]) in a double-blind, placebo-controlled 2x2 factorial trial of three months duration. Change in coronary calcification activity was estimated as a change in coronary maximum tissue-to-background ratio (TBRmax) on 18F-NaF PET. 149 subjects completed follow-up (vitamin-K1: placebo = 73:76 and colchicine: placebo = 73:76). Neither vitamin-K1 nor colchicine had a statistically significant effect on the coronary TBRmax compared with placebo (mean difference for treatment groups 0·00 ± 0·16 and 0·01 ± 0·17, respectively, p > 0.05). There were no serious adverse effects reported with colchicine or vitamin-K1. In patients with type 2 diabetes, neither vitamin-K1 nor colchicine significantly decreases coronary calcification activity, as estimated by 18F-NaF PET, over a period of 3 months. Clinical trial registration: ACTRN12616000024448.